Avaliação das características físicas e biológicas das sementes de urucu c.v. casca verde durante o desenvolvimento da maturação fisiológica. - Lima, Renata Vianna (2005)
The annatto (Bixa orellana L.) is a Bixaceae and its seeds presented low percentage of germination. This work was carried out with the objective to study the maturation and germination of annatto seeds. The experimental follows a completely randomized des